A Study of Work from Home Motivation among Employees - Zamani, Nur Fadzilah Muhamad; Ghani, Madaha Hanafi @ Mohd; Radzi, Siti Fatimah Mohamad; Rahmat, Noor Hanim; Kadar, Nur Syafiqah Abdul; Azram, Aina Athirah Rozman (International Journal of Asian Social Science, 2021)
Many sectors are implementing work from home policy as it is one of the effective ways to avoid physical contact among workers and to control the spread of COVID-19. Amidst the stressful pandemic, working from home poses a different kind of stress among both the employers and employees. Numerous studies have found positive and negative consequences of working from home. With or without the pandemic, working from home has become a new way to work. Some industries cannot function well with their employees working from home. Many are finding ways to make work from home a success. This study explores work from home motivation among 53 employees of different industries. The instrument used is a survey. The survey has 4 sections. Section A has 4 items on demographic profile. Section B has 10 items about availability via flexibility. Section C has 10 items on safety through work-life balance and section D has 10 items on meaningfulness through work performance. Findings reveal interesting motivational influence for employees who work from home.